Bookseller Vasily Ivanovich Lagutkin (1883–1933): A Lishenets’ Biography Reconstruction - Kilin, Alexey P. (Izvestiâ Uralʹskogo federalʹnogo universiteta. Seriâ 2, Gumanitarnye nauki, 2021)
This article analyses the social and economic situation of the citizens deprived of suffrage for engagement in trade during the years of the NEP, with reference to a biography reconstruction of Vasily Ivanovich Lagutkin (1883–1933), an ordinary USSR citizen. The methodological basis of the research is the anthropological approach and a synthesis of macro- and microhistory. The main source of research is the personal file of a citizen who filed a petition to the election commission demanding that his right to vote lost for engagement in trade be restored. The specifics of Lagutkin’s biography are that for 34 years, he was professionally engaged in book trade both in private and in state organisations before and after 1917. The legalisation of private entrepreneurship in 1921 allowed him to start his own business. His trade continued until 1929 and, apparently, was successful, but the process of forced removal of private entrepreneurship from trade led Lagutkin to bankruptcy. Unemployment and high professional mobility in the following years, desperate but unsuccessful attempts to achieve restoration in his right to vote, progressive chronic illness and deterioration of health eventually led to his death in a psychiatric hospital in Perm at the age of 50. Being loyal to the Soviet authorities, expressing a desire to be useful to them, he could not reclaim his right to vote, since the decision to restore it was made on formal grounds which Lagutkin did not meet. The fate of a particular person in the transition era makes it possible to reflect the process of social construction of the “new person”, who, contrary to the declared goals, not only provoked downward social mobility and negative social selection, but in extreme cases led to the death of the individual.